Evaluasi Kurikulum Al-Islam Kemuhammadiyahan di Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Palembang - Anica Anica; Romli Romli; Nyayu Khodijah (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
Changes in the curriculum of al-Islam Kemuhammadiyahan 1 course at the Muhammadiyah University of Palembang became a challenge for lecturers in preparing semester learning plans and implementation of learning to adjust to the National Standards of Higher Education, because in addition to being a national compulsory subject known as Islamic Religious Education with the number 2 credits are also compulsory courses at the University of Muhammadiyah Palembang. This study uses the Countenance evaluation model popularized by Stake, namely two main matrices in the description of descriptions and judgments As for the results of this research found, the documents contained in the al-Islam semester learning plan Kemuhammadiyahan 1 (Islamic Religious Education) have met the criteria of the National Standards of Higher Education but in the learning methods section and assessment indicators do not meet the criteria of the National Standards of Higher Education. While the learning process of the al-Islam Muhammadiyah Center 1 Faculty of Economics and Business shows a discrepancy with the semester learning plan of the Kemuhammadiyahan al-Islamic course due to ineffective use of time in the learning process. And students can understand and try to practice well the basics of the Islamic religion.